Efeitos crônicos da suplementação de Citrulina Malato sobre a força e massa muscular de jovens adultos saudáveis treinados: um ensaio clínico randomizado, cruzado, duplo-cego e controlado por placebo - Estanislau, Thiago Barros [UNIFESP] (2020)
L-citrulline (CIT) is a non-essential amino acid, found in watermelon juice that has the ability to increase endogenous concentrations of arginine (ARG) and markers of nitric oxide (NO) production. The combination and acute use with malate (intermediate of the tricarboxylic acid cycle) has shown promising results in the field of sports nutrition, however the chronic effects are still unknown. This master thesis explored the effects of citrulline malate (CM) supplementation on strength and muscle mass measurements of healthy young adults trained at recreational level. Twenty-four men (age 25.96 ± 4.70 years, body mass 82.25 ± 10.7kg; height 1.79 ± 0.07m and BMI 25.07 ± 2.14m kg/m²) with previous experience in strength training were recruited for this randomized, double-blind, crossover, placebo-controlled study. Each participant consumed 6g of CM or placebo (PLA) at random, 60 minutes before training, for 28 days each, with 1 week of wash-out. The maximum dynamic strength (MDS) was assessed by the one maximum repetition test (1-RM) in the bench press. Body composition was determined by plethysmography. For the statistical analysis, the two-way ANOVA analysis model was used. Significance level equal to or less than 0.05 was considered. Data are represented as mean and standard deviation, or mean and 95% confidence interval (95% CI). The supplementation of CM promoted an increase in fat-free mass (FFM) (pre 67.28 kg ± 8.11 kg vs post 67.77 kg ± 7.97 kg) in relation to PLA (pre 67.83 kg ± 7.84 kg vs post 67, 43kg ± 8.57kg) (CM vs PLA,p = 0.037; CI = 95%: 0.03 - 1.21). Still, in the use of CM there was a reduction in fat mass (FM) (pre 15.10 ± 5.55 vs post 13.85 ± 4.61) in relation to PLA (pre 14.32 ± 5.34 vs post 14.65 ± 5.34) (CM vs PLA, p = 0.30; CI = 95%: -1.24 - -0.06). For FDM, there was an increase in the final load when using both supplements (CM and PLA) (T1: 36.4 (95% CI = 33.0 - 39.8) vs T2: 39.8 (95% CI = 36.4 - 43.2) vs T3 41.8 (95% CI = 38.4 - 45.2) (p = <0.001 in relation to T1 and p = <0.05 in relation to T2.) However, in the use of CM, a greater tendency to increase load was observed in in relation to PLA (p = 0.059). The results show that supplementation of CM for 4 weeks seems to be able to increase FDM and improves body composition, by increase FFM and to reduce FM.